Application of Cabrio (a.i. pyraclostrobin) at flowering and veraison reduces the severity of bitter rot (Greeneria uvicola) and ripe rot (Colletotrichum acutatum) of grapes. (20th March 2014) - Samuelian, S.K.; Greer, L.A.; Savocchia, S.; Steel, C.C.
Abstract Background and Aims Ripe rot (Colletotrichum acutatum) and bitter rot (Greeneria uvicola) are two bunch rot diseases of grapes that occur in warm and wet conditions close to harvest. Management practices for the more commonly occurring bunch rot, Botrytis grey mould, appear to be ineffective for these other bunch rots. Pyraclostrobin has been previously reported to inhibit the growth of the fungi responsible for these rots in vitro. The aim of this work was to evaluate Cabrio (a.i. pyraclostrobin) as a fungicide for bitter rot and ripe rot management in vineyards. Methods and Results The efficacy of Cabrio to control ripe and bitter rots was evaluated over three consecutive growing seasons (2009/10, 2010/11 and 2011/12) on a commercial vineyard with a known history of non‐Botrytis rot pressure. Grapevine flowers and bunches at veraison were treated with Cabrio and artificially infected with C. acutatum and G. uvicola 5 days after fungicide application. Bunches were collected at harvest and the severity of bitter and ripe rot recorded. Cabrio applied at flowering and veraison independently and in combination significantly reduced the incidence of ripe rot. Bitter rot incidence was also reduced in all three growing seasons of the study, but the level of disease control in the 2011/12 growing season was reduced. The 2011/12 season was cooler and wetter compared with the previous 2 years, and these climatic conditions might explain an increase in pathogen pressure. Conclusions Our results demonstrate that an application of Cabrio at flowering, veraison, and at both flowering and veraison reduces the severity of ripe rot and bitter rot at harvest. Significance of the Study The results of this study will assist grapegrowers to develop improved strategies to manage better bitter rot and ripe rot of grapes.